Análise da evasão escolar no ensino técnico: estudo do caso CEFET-RJ - Bastos, Oliver Guimarães Armando (2014)
This dissertation aims to analyze the causes of dropout in technical courses offered by CEFET-RJ. This is a reference institution in high school and technical center located in the Metropolitan Rio de Janeiro, which receives an average of nine hundred students per semester. From literature review on issues related to the learning process, failure and dropout, sought to identify the profiles of dropout students and the causes of their dropout. The concepts discussed here aim to characterize this phenomenon and base the understanding of the topic and the analysis of results. Quantitative and qualitative research was used, document analysis derived CEFET, telephone interviews with dropout students and interviews with teachers and course coordinators, these having been conducted personally. It appears that this institution the social, economic and cultural diversity among students contributes to the multiplicity of causes related to dropout. Continuous improvement processes of teaching, monitoring of students both by institution and by their relatives and prior information about the courses offered make a difference in regard to dropout, thereby decreasing the number of students dropping out every year